The interaction between iodinated X‐ray contrast agents and macrocyclic GBCAs provides a signal enhancement in T1‐weighted MR images: Insights into the renal excretion pathways of Gd‐HPDO3A and iodixanol in healthy mice. Issue 1 (7th March 2022) - Di Gregorio, Enza; Arena, Francesca; Gianolio, Eliana; Ferrauto, Giuseppe; Aime, Silvio
Abstract : Purpose: This work aims to investigate the supramolecular binding interactions that occur between iodinated X‐ray contrast agents (CAs) and macrocyclic gadolinium (Gd)–based MRI contrast agents (GBCAs). This study provides some new insights in the renal excretion pathways of the two types of imaging probes. Methods: The water‐proton relaxivities ( r 1 ) of clinically approved macrocyclic and linear GBCAs have been measured in the presence of different iodinated X‐ray contrast agents at different magnetic field strengths in buffer and in serum. The in vivo MRI and X‐ray CT of mice injected with either Gd‐HPDO3A or a Gd‐HPDO3A + iodixanol mixture were then acquired to assess the biodistribution of the two probes. Results: A significant increase in r 1 (up to approximately 200%) was observed for macrocyclic GBCAs when measured in the presence of an excess of iodinated X‐ray CAs (1:100 mol:mol) in serum. The co‐administration of Gd‐HPDO3A and iodixanol in vivo resulted in a marked increase in the signal intensity of the kidney regions in T1 ‐weighted MR images. Moreover, the co‐presence of the two agents resulted in the extended persistence of the MRI signal enhancement, suggesting that the Gd‐HPDO3A/iodixanol adduct was eliminated more slowly than the typical washing out of Gd‐HPDO3A. Conclusions: The reported results show that it is possible to detect the co‐presence of iodinated agents and macrocyclic GBCAs in contrast‐enhanced MR images. The new information may be useful in the design of novel experiments toward improved diagnostic outcomes.